2020
DOI: 10.1109/access.2020.2968535
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Property Prediction Based on a Multichannel Substructure Graph

Abstract: Molecular property prediction is important to drug design. With the development of artificial intelligence, deep learning methods are effective for extracting molecular features. In this paper, we propose a multichannel substructure-graph gated recurrent unit (GRU) architecture, which is a novel GRU-based neural network with attention mechanisms applied to molecular substructures to learn and predict properties. In the architecture, molecular features are extracted at the node level and molecule level for capt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 51 publications
0
12
1
Order By: Relevance
“…This representation was never applied for RI prediction but gives good results for prediction of other molecular properties. Finally, there are more complex methods for using a deep neural network directly with a molecular graph [47][48][49], such as molecular graph convolutional networks. A molecule can be featurized in many ways, as shown above, and each of these ways can be used as input for a model, and the simultaneous use of various representations and machine learning models will give better results than using only one model and representation [42,45,50].…”
Section: Introductionmentioning
confidence: 99%
“…This representation was never applied for RI prediction but gives good results for prediction of other molecular properties. Finally, there are more complex methods for using a deep neural network directly with a molecular graph [47][48][49], such as molecular graph convolutional networks. A molecule can be featurized in many ways, as shown above, and each of these ways can be used as input for a model, and the simultaneous use of various representations and machine learning models will give better results than using only one model and representation [42,45,50].…”
Section: Introductionmentioning
confidence: 99%
“…A large number of studies have shown that the advantage of deep learning is that it can obtain a robust descriptor of the original data after nonlinear transformation [2], which could promote the model to learn the task-related features from the data. With the establishment of more and more datasets of protein structures and compound-protein interactions, more and more studies have attempted to introduce deep learning methods into both drug discovery [3][4][5] and the predictive task of compound-protein interaction [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al . [ 15 ] proposed a multichannel substructure-graph gated recurrent unit architecture for molecular property prediction and used grid search for hyperparameter optimization. Duvenaud et al .…”
Section: Introductionmentioning
confidence: 99%